The age-related effects on orthodontic tooth movement and the surrounding periodontal environment - Wang, Jiayi; Huang, Yiping; Chen, Feng; Li, Weiran (Frontiers in Physiology, 2024)
Orthodontic treatment in adults is often related to longer treatment time as well as higher periodontal risks compared to adolescents. The aim of this review is to explore the influence of age-related chages on orthodontic tooth movement (OTM) from macro and micro perspectives. Adults tend to show slower tooth movement speed compared to adolescence, especially during the early phase. Under orthodontic forces, the biological responses of the periodontal ligament (PDL) and alveolar bone is different between adult and adolescents. The adult PDL shows extended disorganization time, increased cell senescence, less cell signaling and a more inflammatory microenvironment than the adolescent PDL. In addition, the blood vessel surface area is reduced during the late movement phase, and fiber elasticity decreases. At the same time, adult alveolar bone shows a higher density, as well as a reduced osteoblast and osteoclast activation, under orthodontic forces. The local cytokine expression also differs between adults and adolescents. Side-effects, such as excessive root resorption, greater orthodontic pain, and reduced pulpal blood flow, also occur more frequently in adults than in adolescents.